EXPLORING ACCOUNTING PRACTICE FOR DURIAN PRODUCER LISTED COMPANIES IN MALAYSIA - Mohd Halim Kadri; Saifulrizan Norizan (International Journal of Accounting, Finance and Business, 2022)
The current study aims to explore the accounting practice among durian producer-listed companies in Malaysia. Three durian producer-listed companies were selected as samples. The study's objective was satisfied by examining how the durian industry was reported in the annual reports of these selected companies. In order for local durian producers to survive and increase profitability as well as for the government to reassess its strategy of promoting the durian farming industry, it is timely and vital to have data on the financial performance of this so-called "King of Fruits" industry. There are two issues in this study: first, whether durian as biological assets are recognised as current asset or non-current asset; whether durian plant is recognised as a biological asset or as a property, plant and equipment in financial statement of listed companies. In particular, the study investigated the listed companies' accounting practices for definition, recognition, measurement, presentation, and disclosure of agricultural produce – durian fruits as well as the bearer plants – durian trees. This paper begins with an overview of the durian industry in Malaysia and the accounting regulatory framework that applies in Malaysia. Next, the requirements of MFRS 141- Agriculture as applied to agricultural produce - durian fruits and MFRS 116 - Property, Plant, and Equipment in relation to durian trees as bearer plants are reviewed. Then, the findings are briefly discussed. This paper ends with a review of how the new durian producers might present the fair value gains and losses related to agricultural produce in their financial statements in accordance with the relevant MFRSs. The findings revealed that the selected three durian producer-listed companies defined, recognised, measured, presented, and disclosed the growing agricultural produce - durian fruits and durian trees in accordance with the Malaysian Financial Reporting Standards, mainly MFRS 141 - Biological assets and MFRS 116 - Property, Plant and Equipment, respectively. The results of the current study contributed to knowledge in the area of agriculture accounting. The results will provide guidelines of accounting practice on durian to new durian producer-listed companies.